Cariview test와 전문가 칫솔질 교육이 치위생(학)과 신입생의 PHP index 감소에 미치는 효과 - 김연화; Youn-hwa Kim; 김유근; Yu-geun Kim; 유진아; Jin-ah Yoo; 박정은; Jung-eun Park (Han'guk Ch'iwisaeng Hakhoe chi, 2017)
Objectives: This study was conducted to examine the effectiveness in oral health promotion through oral health education for freshmen students of the dental hygiene department. Methods: To verify its effectiveness, research was conducted on 74 freshmen of the dental hygiene department by the evaluation of DMFT index, PHP index, and Cariview test (2015-2016). Results: The analysis of the test results using Cariview equipment shows a categorization of low risk group consisting of 10 students (13.5%), middle risk group consisting of 47 students (63.5%), and a high risk group consisting of 17 students (22.9%). DT index according to the number of daily tooth brushing by <2 is DT index average score higher and in such a case, statistics are considered meaningful (p<0.01). Oral health state at DMFT index of low risk group according to Cariview risk group for an analysis is lower than both the middle risk group and the high risk group (p<0.001). Conclusions: A review of the effect of the promotion of oral health through oral health education on the behavior change rather than of Cariview test and value of dental plaque through tooth brushing method was conducted.